1983
DOI: 10.18785/negs.0602.04
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Relationships of Fishes Occurring Within a Surf Zone Habitat in the Northern Gulf of Mexico

Abstract: We studied trophic relationships of Florida pompano (Trachinotus carolinus), gulf kingfish (Menticirrhus littoralis), scaled sardine (Harengu/a jaguana~ striped anchovy (Anchoa hepsetus) and dusky anchovy (A. /yo/epis) during their spring residency in the Horn Island, Mississippi, surf zone. Harengu/a jaguana, A. /yo/epis and A. hepsetus were zooplanktivores, utilizing primarily calanoid copepods, mysids and various decapod larvae. Menticirrhus /ittoralis and T. caro/inus utilized benthic prey including Donax,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
61
2
9

Year Published

1990
1990
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 13 publications
(14 reference statements)
10
61
2
9
Order By: Relevance
“…A greater efficiency in the early morning low tide capture occurred, not only in this work, but also in the samplings performed by LASIAK (1984). In other areas, despite the absence ofcorrelation with the tide, again a greater number of individuals were present in the early morning catches (MODDE & Ross 1981;Ross et of. 1987).…”
Section: Discussionsupporting
confidence: 56%
“…A greater efficiency in the early morning low tide capture occurred, not only in this work, but also in the samplings performed by LASIAK (1984). In other areas, despite the absence ofcorrelation with the tide, again a greater number of individuals were present in the early morning catches (MODDE & Ross 1981;Ross et of. 1987).…”
Section: Discussionsupporting
confidence: 56%
“…Harengula clupeola não apresentou um padrão definido com relação às zonas de batimento, tendo apresentado pico na zona abrigada no outono e na zona muito exposta na primavera. Isto pode ser devido ao seu hábito planctófagos, portanto não dependente exclusivamente do gradiente de exposição às ondas e, sim relacionado ao movimento das correntes associados à renovação rápida dos recursos planctônicos (Modde & Ross 1983). Umbrina coroides também apresentou ampla distribuição em relação ao nível de batimento, sendo associada à zona abrigada na primavera e à zona exposta no inverno.…”
Section: Discussionunclassified
“…Umbrina coroides também apresentou ampla distribuição em relação ao nível de batimento, sendo associada à zona abrigada na primavera e à zona exposta no inverno. Trachinotus carolinus, por outro lado, ocorreu com uma maior abundância na zona abrigada durante a primavera embora seja citada como uma espécie típica de zonas expostas (Modde & Ross 1983). Esta espécie é praticamente ausente das praias arenosas no interior da Baía de Sepetiba, embora ocorra em abundância em praias adjacentes a esta baía (Pessanha et al 2000).…”
Section: Discussionunclassified
“…Estuarine fish communities represent a combination of freshwater and marine species that live on the threshold of its distribution, other estuarine residents and migrants that reach the estuarine zone at spawning or feeding season (Maes et al, 1998;Cardona, 2000). With the nearshore coast, surf-zones and estuaries of tropical and temperate zones act as nursery, providing abundant food resources (Modde and Ross, 1981) and protection against predators (Anderson et al, 1977). As an important beach modeler (Hoefel, 1998) and transporter of organic matter and nutrients between continent and sea (Yañez-Aranciabia, 1978), the surf-zones support a widely fauna, mainly zooplankton and fishes (Maes et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been observed that environmental complexity in terms of wave exposure and microhabitats formation, like seagrass and reefs, are related to composition and dynamics of surf-zone fish assemblages (Clark et al, 1996;Clark, 1997). Surf-zone ichthyofauna are both seasonal and diel dynamic (Modde and Ross, 1981). Lasiak (1984) accepted that surf-zones concentrated a wide ichthyofauna, relatively high species richness, comparing to better-known environments, like estuaries and shelf.…”
Section: Introductionmentioning
confidence: 99%